FACTORS INFLUENCING DECISION MAKING TO CONDUCT PAID PROJECTS OF GEOGRAPHY EDUCATION STUDENTS, UNIVERSITY OF JEMBER - Aroby, Kholifi - (JURNAL SOCIUS, 2025)
There are various factors that influence decision making in undertaking paid projects for students. One of them is the influence of consumerism, this article aims to analyze the factors influencing consumerism on students. Students' decisions in taking paid projects as an effort to meet financial and lifestyle needs. This study uses a quantitative approach by collecting data through a survey of Geography Education students, University of Jember. From the results of the data obtained, it shows that non-paid projects are highly anticipated, because they do not need to spend a penny and get almost equivalent benefits. The minimum weekly money is the main factor for students in whether or not to participate in a paid project. In addition, to meet the needs of life is often a conflict for students to get involved in paid projects. This study provides insight into the importance of time management and wise decision making so that students can balance financial needs and academic responsibilities.